2018
DOI: 10.3390/rs10111735
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Tree-Related Microhabitats in TLS Point Clouds Using Machine Learning

Abstract: Tree-related microhabitats (TreMs) play an important role in maintaining forest biodiversity and have recently received more attention in ecosystem conservation, forest management and research. However, TreMs have until now only been assessed by experts during field surveys, which are time-consuming and difficult to reproduce. In this study, we evaluate the potential of close-range terrestrial laser scanning (TLS) for semi-automated identification of different TreMs (bark, bark pockets, cavities, fungi, ivy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…The great number of plots and their distribution in the landscape required a very efficient sampling design, which is time-effective as well. Further advances in sensor technologies with very dense aerial or UAV LiDAR might overcome these shortcomings of incomplete representation of the geometry of the stand and make new structural indices or the full detection of TreMs possible [38,74]. The sampling effort of the different methods (manual inventories, UAV, mobile or terrestrial RS) differs strongly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The great number of plots and their distribution in the landscape required a very efficient sampling design, which is time-effective as well. Further advances in sensor technologies with very dense aerial or UAV LiDAR might overcome these shortcomings of incomplete representation of the geometry of the stand and make new structural indices or the full detection of TreMs possible [38,74]. The sampling effort of the different methods (manual inventories, UAV, mobile or terrestrial RS) differs strongly.…”
Section: Discussionmentioning
confidence: 99%
“…While different RS-and TreM-based studies have shown promising results for the quantification of diversity of different taxa [1,3,13,38], their potential as combined descriptors of biodiversity had not yet been researched. As technical progress advances, new options for the detection of particular TreMs at very fine scales will become available [38], and information on the most applicable set of predictors can help to identify the most objective, cost and time efficient inventory methods for the selection of key retention elements as habitat trees for forest biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from the Swiss Federal Research Institute WSL shows how data from Terrestrial Laser Scanning could be useful for identifying TreMs, through their inclusion in the National forest inventory (Rehush et al 2018). Additionally, recent improvements in the use of Airborne Laser Scanning data for monitoring forest resources, especially single tree detection, could be useful for mapping tallest and largest trees that often correspond to habitat trees.…”
Section: Speciesmentioning
confidence: 99%
“…To our knowledge, there is no common agreement on the setup of the scanning design [30], but at least some specifications (minimum distance to the next tree, height above ground, vegetation phase) may be beneficial to gain comparable results. Further research needs to be done to directly detect and quantify additional structural features like canopy gaps [43], or TreMs [44], that are not ideally represented by the SSCI.…”
Section: Data Aquisition and Availabilitymentioning
confidence: 99%